Método de inversão para a obtenção dos parâmetros elétricos do solo para região amazônica baseado em medições e usando equações parabólicas - OLIVEIRA, Romulo Augusto Nascimento de (Universidade Federal do Pará, 2017)
In recent years, due to the rapid development of the technology of radio access digital such as TV Digital and digital audio broadcasting, accompanied by a strong demand for these types of services, it has become of great importance the study the electric field behavior generated by radio stations who will use these technologies as well as knowledge of electrical parameters involved, which are essential in determining of the stations coverage area. This work presents a methodology of inversion through weighted least squares to obtain the equivalent electrical parameters of the vegetation and soil of a typical Amazon forest region using the model based on the formalism of parabolic equations to calculate the electric field strength received by a mobile receiver contained within in this region. To validate this methodology, measurement campaigns were conducted in Benfica, Marituba and Barcarena, State of Pará. Since in Benfica and Marituba was used a frequency of 900 MHz and Barcarena was used the frequency of 1.8 GHz. For the three cities, the measuring system consisted of a laboratory fixed and a mobile station that has been set up to measure and store the instantaneous values of the received signal. The measurements were compared with computer simulations, and so it was possible to estimate the optimal values for the electrical conductivity and relative permittivity of the vegetation that cut the road access to the cities and of the highway soil through the proposed inversion methodology. It was also made a quantitative analysis of these parameters with the values found in the literature which demonstrated the effectiveness of the proposed methodology. Finally, this work presents the results obtained with the inversion method for a rural region located in the center of Brazil, where it was found that the estimated values for soil electrical conductivity were very close to those shown in recent studies to the region.